BUMDES Management Training in Sei Bamban District Based on Cognitive Cointegration Method - L, Lilinesia; Mariani Sinurat, Yenni; Syafrizal, Rodi; Nur Ilham, Rico (RADJA PUBLIKA, 2021)
Currently the government continues to strive to build and develop the economy of rural areas through community empowerment programs with the aim of increasing productivity, business diversity and regional potential with the aim of improving the economy and welfare of rural communities. One of the government programs is by providing a budget. Funds in the field of community empowerment are used to support capital for the formation of Village Owned Enterprises (BUMDes). Where in accordance with the objectives of BUMDes, namely optimizing the management of village assets and the potential of existing villages, to support the village economy, and improve the welfare of the village community. But unfortunately, until now the role and function of my BUMDes has not been effective and cannot be felt by the community. This is due to the incompetence and lack of professionalism of human resources managing BUMDes and the lack of integration of the businesses managed by BUMDes with the existing village potential so that it seems as if BUMDes stands only as a formality without supporting the economic potential of rural communities. The purpose of this study is to create a strategic concept in the management of BUMDes so that it runs more effectively and according to targets so that it can support the economy of rural communities through the development of human resource knowledge in managing BUMDes that is integrated with the economic potential of rural communities. So that BUMDes and Village Basic Pontesials are integrated in a business institution that supports the village economy for the welfare of the village community. This solution can help rural communities in strengthening their economy and provide knowledge views and open insight to BUMDes managers so that they can develop BUMDes into businesses that are in synergy with the community. This study uses primary data sourced from questionnaires and interviews aimed at BUMDes management employees to see the extent to which the abilities, expertise, and knowledge of BUMDes management employees can evaluate and innovate in the business.